RETRACTED: The Mechanism of Pertussis Cough Revealed by the Mouse-Coughing Model - Yukihiro Hiramatsu; Koichiro Suzuki; Takashi Nishida; Naoki Onoda; Takashi Satoh; Shizuo Akira; Masahito Ikawa; Hiroko Ikeda; Junzo Kamei; Sandra Derouiche; Makoto Tominaga; Yasuhiko Horiguchi (mBio)
ABSTRACT Pertussis, also known as whooping cough, is a contagious respiratory disease caused by the Gram-negative bacterium Bordetella pertussis. This disease is characterized by severe and uncontrollable coughing, which imposes a significant burden on patients. However, its etiological agent and the mechanism are totally unknown because of a lack of versatile animal models that reproduce the cough. Here, we present a mouse model that reproduces coughing after intranasal inoculation with the bacterium or its components and demonstrate that lipooligosaccharide (LOS), pertussis toxin (PTx), and Vag8 of the bacterium cooperatively function to cause coughing. Bradykinin induced by LOS sensitized a transient receptor potential ion channel, TRPV1, which acts as a sensor to evoke the cough reflex. Vag8 further increased bradykinin levels by inhibiting the C1 esterase inhibitor, the major downregulator of the contact system, which generates bradykinin. PTx inhibits intrinsic negative regulation systems for TRPV1 through the inactivation of Gi GTPases. Our findings provide a basis to answer long-standing questions on the pathophysiology of pertussis cough. IMPORTANCE The Gram-negative bacterium Bordetella pertussis causes a respiratory disease called whooping cough, or pertussis. This disease is characterized by paroxysmal coughing, the mechanism of which has not been intensively studied because of a lack of versatile animal models that reproduce the cough. In this study, we present a mouse model that reproduces coughing after intranasal inoculation with the bacterium or its components. Using this model, we demonstrate that lipooligosaccharide, Vag8, and pertussis toxin of the bacteria cooperatively function to cause coughing. Our results also indicate that bradykinin, an inflammatory mediator, and TRPV1, an ion channel linked to nociceptive signaling, are host factors involved in the coughing mechanism.